Tolerancja na dwuznaczność a poziom zadowolenia z życia młodzieży niedowidzącej - Kędzierska, Bogna (Acta Universitatis Lodziensis. Folia Psychologica, 2007)
Intolerance of ambiguity (the concept formulated by E. Frenkel-Brunswik in 1948) we can concern as emotional and cognitive dimension of personality. It is characterized by seeking for certainty, clear structure and avoiding ambiguity. This article presents research analyzing, if specific experience of adolescents with low vision (who can fluctuate between seeing and not seeing and have to functioning with not clear and fragmental picture of reality) affected on their intolerance of ambiguity and haw is important the level of tolerance of ambiguity for subjective well-being.